1982
DOI: 10.1159/000459047
|View full text |Cite
|
Sign up to set email alerts
|

Guanylate Cyclase Activity in Human Leukemic and Normal Lymphocytes

Abstract: Cyclic GMP is thought to be involved in lymphocytic cell proliferation and leukemogenesis. In general, the nucleotide is elevated in leukemic vs. normal lymphocytes and changes have been reported to occur during remission and relapse of this disease. Although the cA/cG ratios are higher for normal lymphocytes the basal guanylate cyclase (EC 4.6.1.2) activities do not correlate with altered cyclic GMP levels. The crude guanylate cyclases display classical Michaelis-Menten kinetics with Kms for Mn-GTP of 463 pmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…cAMP and cGMP were thought to act as biological antagonists in the regulation of cell growth at the beginning (Goldberg et al, 1975), and elevated cGMP levels have been observed in certain human tumor tissues (Hadden et al, 1972;DeRubertis et al, 1976;Takemoto et al, 1982). Increased urinary cGMP in rats with hepatoma or renal tumor implants was also detected by Murad et al (1975) and Criss and Murad (1976).…”
Section: Discussionmentioning
confidence: 99%
“…cAMP and cGMP were thought to act as biological antagonists in the regulation of cell growth at the beginning (Goldberg et al, 1975), and elevated cGMP levels have been observed in certain human tumor tissues (Hadden et al, 1972;DeRubertis et al, 1976;Takemoto et al, 1982). Increased urinary cGMP in rats with hepatoma or renal tumor implants was also detected by Murad et al (1975) and Criss and Murad (1976).…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-and beta-momorcharin, momordin, and cucurbitacin B from MC have clinically demonstrated ability to inhibit guanylate cyclase linked to pathogenesis and replication of leukemia and other cancers (Takemoto et al, 1982b).…”
Section: Experimental Studiesmentioning
confidence: 99%
“…MC has demonstrated the ability to inhibit an enzyme named guanylate cyclase in a clinical setting (Takemoto et al, 1982b). A conjugate of momordin, monoclonal antibody (named 8A) and plasma antigen was tried for ex vivo purging in autologous bone marrow transplantation in multiple myeloma patients.…”
Section: Clinicalmentioning
confidence: 99%
“…Whole fruit aqueous extracts of a Chinese bitter melon have displayed preferential cytotoxicity towards breast cancer and leukemia cells, without effecting the viability of normal cells. 29, 30 Similarly, saponin-rich extracts selectively induced apoptosis in hepatoma cells, without causing the same effect in their normal counterparts. 31 In this study, the SE did not discriminate in its cytotoxic activity and, in fact, was more potent to the HPDE cells.…”
Section: Discussionmentioning
confidence: 99%